Effects of pre-strain and annealing on the fatigue properties of complex phase steel CP800. (February 2020) - Sun, Haofei; Wei, Kai; Yang, Xujing; Xiao, Zhi; Wu, Yazhuo
Graphical abstract: Highlights: The effective range of pre-strain to improve yield and tensile strengths of CP800 steel. Pre-strain has a negative effect on the fatigue properties, while the annealing treatment will improve the fatigue life. Two kinds of failure modes caused by surface defects and inclusions were observed. A model based on strain energy is established to predict the fatigue life of CP800 steel. Abstract: This work was to experimentally explore the fatigue properties under the conditions of pre-strain and annealing for CP800. Meanwhile, the elongation of grains caused by pre-strain and the increase content of bainite and martensite caused by annealing were observed by using optical microscopy (OM) and scanning electron microscopy (SEM), respectively. An effective pre-strain range was found to increase the yield and tensile strengths by dislocation strengthening. Besides, the pre-strain presents a negative effect on fatigue life, while the fatigue life can be increased by annealing treatment. It is confirmed that the combined effect of the large pre-strain and annealing treatment leads to cyclic hardening fracture. Furthermore, two kinds of failure modes caused by surface defects and inclusions were revealed by using SEM. Eventually, the fatigue life can be well predicted with a model based on strain energy method.